2013
DOI: 10.1186/1476-9255-10-26
|View full text |Cite
|
Sign up to set email alerts
|

A hexadecylamide derivative of hyaluronan (HYMOVIS®) has superior beneficial effects on human osteoarthritic chondrocytes and synoviocytes than unmodified hyaluronan

Abstract: BackgroundIntra-articular hyaluronan (HA) injection provides symptomatic benefit in the treatment of osteoarthritis (OA). Previously we found superior beneficial effects in a large animal OA model of a hexadecylamide derivative compared with unmodified HA of the same initial molecular weight. The current study sought to define possible molecular mechanisms whereby this enhanced relief of symptoms was occurring.MethodsChondrocytes and synovial fibroblasts were isolated from tissues of patients undergoing arthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 53 publications
(78 reference statements)
0
35
0
3
Order By: Relevance
“…Different formulations of HA are produced and crosslinking strategies are used to control HA degradation and mechanical properties. An hyaluronan amide derivative (HAD) of 500–730 kDa has been produced via amidation of the polymer carboxyl groups by long chain alkylamine (98% remains unmodified HA) to enhance the rheological properties and to increase the residence time in the joint cavity compared with non‐amidated unmodified HA (HYAL; Smith, Russell, Schiavinato, & Little, ).…”
Section: Introductionmentioning
confidence: 99%
“…Different formulations of HA are produced and crosslinking strategies are used to control HA degradation and mechanical properties. An hyaluronan amide derivative (HAD) of 500–730 kDa has been produced via amidation of the polymer carboxyl groups by long chain alkylamine (98% remains unmodified HA) to enhance the rheological properties and to increase the residence time in the joint cavity compared with non‐amidated unmodified HA (HYAL; Smith, Russell, Schiavinato, & Little, ).…”
Section: Introductionmentioning
confidence: 99%
“…A frequently encountered debate in the literature addresses the molecular weight (MW) of the HA product injected. It was previously demonstrated that HA products with a MW of 500-730 kDa pass easily through the synovial membrane stimulating the endogenous synthesis of HA [23]. It is also specified that this may lead to a large quantity of high molecular HA to be secreted in the synovial liquid [24].…”
Section: Discussionmentioning
confidence: 99%
“…VAS is a consistent and validated instrument in measuring chronic pain intensity [21,22,23]. As 38% of Mures population consists of Hungarians [24], the questionnaires used in the study were translated into two languages: Romanian and Hungarian.…”
Section: Methodsmentioning
confidence: 99%